Green mobile devices and networks : energy optimization and scavenging techniques - Venkataraman, Hrishikesh.; Muntean, Gabriel-Miro, 1972- (CRC Press, 2012)
"Powering the astounding functional advancement of mobile devices requires a revolution in the concept of battery life and recharge capability. This book provides insight into the principles and technical challenges behind automatically optimizing energy consumption in a dynamic real-time scenario. It discusses the continuous monitoring of battery life and the automatic adjustment of different functionalities including the reception mechanism, the complexity of the software modules, and the perceived video quality. It deals with different energy scavenging techniques and the technologies behind harvesting energy through sources like solar, light, acoustics, kinetic, mechanical vibrations, and electromagnetic waves"--